Antisense SCL suppresses self-renewal and enhances spontaneous erythroid differentiation of the human leukaemic cell line K562. - Green, A R (1991)
The SCL gene encodes a member of the helix-loop-helix family of transcription factors that have been implicated in regulation of differentiation and development. Although SCL mRNA is not detectable in normal thymocytes or peripheral T-lymphocytes, transcriptional activation occurs in T-cell tumours. A clue to the normal function of SCL has come from demonstration of high levels of SCL mRNA in erythroid cells. To illuminate the function of SCL in the erythroid lineage, an antisense SCL construct was introduced into the human erythroleukaemia cell line, K562. Cells electroporated with a vector containing antisense SCL grew more slowly than control cells which had received vector alone. Non-specific toxicity was excluded by showing that antisense SCL did not influence growth of Raji cells, a B-cell line that does not express endogenous SCL mRNA. Suppression of K562 growth was accompanied by increased spontaneous erythroid differentiation as measured by benzidine staining. K562 cells containing antisense SCL produced smaller colonies in agar and exhibited reduced clonogenicity compared with control cells. In addition, experiments in which K562 colonies were recloned showed that antisense SCL profoundly suppressed self-renewal of K562 cells. These data provide the first evidence that SCL promotes self-renewal in an erythroid cell line and raise the possibility that SCL may function to regulate proliferation of normal erythroid cells.